On the functional capacity of the ypophysis disconnected from the hypothalamus (Revista Española de Fisiología, 1960)
An experimental study is made on the functional capacity of the adenohypophysis after that is desconected neurally andvascularly of the hypothalamon. This study is made in normal conditions of life and in stress situation, in guinea-pigs.Method. The hypophysis is desconected of the hypothala mon destroying, by electrocoagulation, the infundibulum according to a stereotaxic method, previously described by the Author (19,20). So it is impossible the regeneration of the special vessels of the contact surface between infundibulum and adenohypophysis.The localization of the provoked lesions was investigated by means of serial sections of the diencephalon.Material- The material employed in this experiences is exposed in the following sinoptic table.In the experience II, diphteria toxin was injected to the guinea-pig 4 days after the infundibular electrocoagulation.In experience I the functional picture of both the adreanal glands and testes was evaluated on a morphological and histo-chemical basis. Special attention was given to the nuclear vo lunte variations of the cells of the fasciculata externa and interna of the adrenal cortex and of the Leydig cells of the testis. The diameter of the seminiferous tubules was also me- sured. All of these data were compared with from 5 male gui- nea-pigs of the same age, mantained in similar conditions, which served as a control group.The experience II is based in the feature that was described by TonutTI : a guinea-pig that is injected with 5 1. m. d. of diphteria toxin dies with a hemorrhagic necrose of adrenal glands. A guinea-pig that receive simultaneously both 5 1. m. d. of diphteria toxin and cortisone, or was hypophysectomized a month before, dies, but their adrenal glands are normal.RESULTS. The results of both experiences are summarized in the following table, showing the mean valúes of theparameters studied :The comparison of data of the experience I, reveáis very little variátions between both groups (control and experimen tal) the conclusión reached is that in the animáis not submitted to a stressing situation, the hypothalamo-hypophyseal descon- nection, both neural and vascular, does not incite an appreciable change in the function of both the adrenal cortex and testis.The results obtained in the experience II suggest that the adenohypophysis can respond to a stress stimulus, with a in crease in secretion of ACTH, although the contact surface be destroyed but this secretion in smaller than in in the controlgroup.The discordant firidings published by others Authors are probabljr atribuable to the lesión of some neighbouring nucleiin the median eminence which function as hypothalamo-adre- nocorticotropic and gonadotropic centers.